Growth and instability in area, production and yield of major spice crops in Rajasthan vis-à-vis India - Meena, R C Kumawat, P C (Journal of Spices and Aromatic Crops, 2005)
A study on growth and instability in area, production and yield of spice crops such as coriander (Coriandrum sativum), cumin (Cuminum cyminum), fenugreek (Trigonella foenumgraecum), fennel (Foeniculum vulgare), garlic (Allium sativum) and chilli (Capsicum annuum) in Rajasthan vis-à-vis India indicated that almost all the spices registered significant growth rates in their production in Rajasthan as well as in India during the entire study period mainly due to significant increases in the same during post-Technology Mission on Oilseeds (TMO) period (1986-87 to 2000-01). The significant increase in production in coriander was mainly due to significant increase in yield whereas in cumin and fennel, it was due to significant increase in area. In fenugreek, the increase in production was the result of increase in both area and yield. In case of chilli and garlic, both area and yield at the national level and only area at the state level played significant role in increasing the production. In majority of the spice crops the instability in production increased during the post-TMO period over the pre-TMO period (1967-68 to 1985-86) in Rajasthan and India as well. However, the magnitudes of coefficients of variations were more pronounced at the state level than at the national level. The instability in area in the state was higher in the post-TMO period than in the pre-TMO period. The same was true of India except that the magnitudes of coefficients of variations were less at the national level. In general, yield instability, on the other hand, decreased during the post-TMO period over the pre-TMO period in both Rajasthan and India. As regards sources of variance of production, area variance played a dominant role in case of coriander, cumin, fennel and garlic. Yield variance predominantly destabilised the production of chilli in Rajasthan and of fenugreek in India. In majority of spices, areayield covariance helped stabilize the production in Rajasthan as well as in India.